KAJIAN SUSEPTIBILITAS MAGNETIK PASIR BESI PANTAI ARTA SEBAGAI FUNGSI JARAK DARI TEPI LAUT - Irma Novalia; Erwin Erwin (Komunikasi Fisika Indonesia, 2020)
Magnetic Susceptibility measurements and the identification of elements of iron sand from Arta beach of Pariaman West Sumatera have been done. The samples were dried first under the sun before the separation between magnetic particles of iron sand and non-magnetic particles using Iron Sand Separator. Identification elements of iron sand was done using X-Ray Fluorescence. The total value of magnetic induction was measured using a magnetic Pasco probe PS-2162 using a solenoid 2000 coils turns, dimensions of 3 cm in diameter and 10 cm in length. The solenoid was given an electric current with variations ranging from 2 A – 8 A. The distance between magnetic probe and one end of solenoid was kept constant that was 1 mm. The next experiment was to measure the function of distance ranging from 1 – 5 mm with constant applied current of 8 A. When electric current increase then the total magnetic induction also increase. Total magnetic induction value decreases as the distance increases. Magnetic susceptibility was calculated based on total magnetic induction and magnetic induction of core currents with constant current of 8 A and distance of 1 mm. The value of magnetic susceptibility obtained in the range (2164,71-3159,99)x10-5 which consist of ilmenite mineral (FeTiO3; Antiferromagnetic).Keywords :  iron sand, magnetic suseptibility, iron sand separator, solenoid, magnetic induction, and  x-ray fluorescence.